Sebaran Tumbuhan Bawah Bekas Injakan Banteng (Bos javanicus d’Alton), Kerbau Liar (Bubalus bubalis), dan Rusa (Cervus timorensis) di Taman Nasional Baluran - Suhadi, Suhadi; Alikodra, Hadi S. (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
National Park is a nature conservation area has a wild  ecosystem and managed by zone system. Baluran National Park (BNP) is one of conservation area in Indonesia covered 25,000 hectare consists of 420 hectare of Bekol’s savanna and 150 hectare of Bama’s savanna. From  4.345 grass-feeding mammal  in BNP, it has estimated that their total weight about  777,000 kg  and  the total feeding need  about 77,700 kg  per day. On the other hand, the biomass of the grasslands only 86.125 kg/ha/day, and both Savannas could only produce biomass about 40,478.75 kg  per day which was  not enough to support the daily animal feeding. Decreasing of the biomass in BNP was assumed as a result of habitat destruction by animal step printings.  The purpose of  this study is to know the effect of animal step printing to the biomass production.  Samples was taking from April to December 1999 using quadrates method which was applied following the animal step printing and the control (non-stepped area). The plant samples were kept in plastic pocket and then identified  in the laboratory. The total  number of quadrates could be detected in this study were 150.  From this study it was concluded that  Grassland which was stepped by banteng, water buffalo and deer  decreased the number of plant species  until 38.88%, 27.27% and 18.18% respectively.